Metode Pembagian Warisan - Syafrida Ayu Sari; Zainal Efendi Hsb (Bhinneka: Jurnal Bintang Pendidikan dan Bahasa, 2025)
The division of inheritance is a crucial process carried out after someone passes away to manage the assets left behind, involving the testator, heirs, and the inherited property. In Islamic law, this division is regulated based on the Quran and Hadith with the aim of preventing disputes among heirs. This process must comply with the applicable legal requirements, including Law No. 3 of 2006 on religious courts. This research employs a qualitative descriptive approach by collecting data from the works of scholars in the field of uṣūl fiqh. The findings explain the definitions and divisions of dzawil furudh, ashabah, and dzawil arham, as well as the proportion of inheritance shares determined by Islamic law, such as half (1/2), one-quarter (1/4), and two-thirds (2/3). Wise management of inherited assets is essential to fulfill family responsibilities and avoid legal violations.